2010
DOI: 10.4061/2010/302731
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Methylation by EcoP1I DNA Methyltransferase

Abstract: EcoP1I DNA MTase (M.EcoP1I), an N6-adenine MTase from bacteriophage P1, is a part of the EcoP1I restriction-modification (R-M) system which belongs to the Type III R-M system. It recognizes the sequence 5′-AGACC-3′ and methylates the internal adenine. M.EcoP1I requires Mg2+ for the transfer of methyl groups to DNA. M.EcoP1I is shown to exist as dimer in solution, and even at high salt concentrations (0.5 M) the dimeric M.EcoP1I does not dissociate into monomers suggesting a strong interaction between the monom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…the P1 prophage-encoded type III M.EcoP1I. This MTase modifies ss- and dsDNA (similar K m and k cat ) with comparable efficiency and it was shown that ssDNA methylation is not linked with formation of double stranded structures 34 , 35 . Such unusual phage MTase feature may be related to the survival of single-stranded DNA phages in bacterial host 35 .…”
Section: Discussionmentioning
confidence: 99%
“…the P1 prophage-encoded type III M.EcoP1I. This MTase modifies ss- and dsDNA (similar K m and k cat ) with comparable efficiency and it was shown that ssDNA methylation is not linked with formation of double stranded structures 34 , 35 . Such unusual phage MTase feature may be related to the survival of single-stranded DNA phages in bacterial host 35 .…”
Section: Discussionmentioning
confidence: 99%